2017
DOI: 10.1002/adem.201700610
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Strength Evolution and Damage Mechanisms of Al–Si Piston Alloy at Different Temperatures

Abstract: The Al-Si piston alloys always bear different temperatures because of its peculiar component structure and service condition. Therefore, the tensile strength, elongation to fracture, and corresponding damage mechanisms of Al12SiCuNiMg piston alloys (ASPA) have been investigated with in situ technique at different temperatures. The tensile properties show two-stage tendencies: the former stage (25-280 C) is determined by easily broken phases with inherent brittleness (such as primary Si), and the fracture behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…This is in agreement with previous reports in which an increase in the fraction of decohesion between Si/matrix interfaces and matrix damage in shape of voids was also observed after deformation of Al-Si alloys at elevated temperature [33,34,38,39,40]. Decohesion is known to result from accumulation of plastic deformation of the matrix in the vicinity of rigid phases, while fracture of rigid particles occurs owing to incompatible stresses between rigid phase and matrix [33].…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with previous reports in which an increase in the fraction of decohesion between Si/matrix interfaces and matrix damage in shape of voids was also observed after deformation of Al-Si alloys at elevated temperature [33,34,38,39,40]. Decohesion is known to result from accumulation of plastic deformation of the matrix in the vicinity of rigid phases, while fracture of rigid particles occurs owing to incompatible stresses between rigid phase and matrix [33].…”
Section: Discussionsupporting
confidence: 93%
“…Al alloys, a recyclable material, are playing an important role in the national economic development because of its excellent comprehensive performance. [ 1 ] Among them, Al–Si alloys, such as the ZL109 Al alloy, are widely used as piston heads and pin bosses in engines, [ 2,3 ] due to its high strength to weight ratio, low thermal expansion coefficient, good thermal conductivity, and corrosion resistance. [ 4–6 ] Iron is the most common harmful impurity to restrict the recycling of Al–Si alloys, due to the large size Fe‐rich intermetallic produced during each cycle process.…”
Section: Introductionmentioning
confidence: 99%
“…Even for a pure polycrystalline material, one can distinguish ductile and brittle fracture, voids growth, transgranular and intergranular failure, shear band decohesion, crack nucleation due to twin interaction [1][2][3][4][5]. Non-homogeneous materials, such as metal-matrix composites, envisage yet a larger spectrum of failure modes, including cleavage of brittle particles embedded in a ductile matrix and matrix-particle decohesion [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In this framework, the numerical simulations were mainly based on the "void cell computations" suggesting either periodic arrays of cells with spherical particles or more complex (but also regular) arrangements including several families of cells of different size, cells containing several voids, and variation of the voids shape [26][27][28][29][30][31]. On the other hand, numerous experiments showed that the fracture of composites depend on the heterogeneous distribution of particle sizes, shapes, and interparticle spacing, as well as the associated topology of the second phase [6][7][8][9][10][11][12][13][16][17][18][19][20][21][22][32][33][34]. Models considering real particle arrangements made it possible to examine the role of the material heterogeneity, in particular, the particles clustering and complex interconnected topologies, as well as the statistical aspect of fracture [17,[35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation